O trabalho na edição de materiais didáticos: uma perspectiva ergológica - Jorge, Loren Kellen Carvalho (2023)
In this research, we investigate the intermediations and the editorial practices of teaching materials production, based on the ergological perspective. The general goal is to understand the profile of editorial intermediaries and their editorial practices in the educational segment. The general objective is broken down into the following specific objectives: reflect on the fields of editing and education through the ergological perspective; understand editorial practices, activities, and their intermediaries; identify the profile of professionals that work in the teaching materials production; analyze the editorial practices and activities of this group of professionals through the ergological viewpoint; and identify the conception features of teaching materials. The theoretical framework presents the main authors that study ergology, such as Yves Schwartz (2010, 2014 e 2018), and Louis Durrive (2011 e 2018), combined with theoretical references dedicated to the history of textbooks and editorial production, including Roger Chartier (1996, 2011), Robert Darnton (1990), José de Souza Muniz Júnior (2010 e 2018), and Luciana Salazar Salgado (2016 e 2017). Thus, this research aims to systematize conceptual aspects of the ergological perspective, highlighting contributions to the triad of work, education, and editing. To achieve the objectives outlined, we sought, using a methodological approach we developed based on the ergological perspective, to analyze the interventions and practices through work activity and ergological concepts, for example, the discussion of norms and renormalization. From data collection, consisting of an electronic questionnaire and semistructured interviews, we analyzed the speeches of editing intermediaries using the Content Analysis method (BARDIN, 2011), and identified 28 primary categories that refer to aspects of the editorial activity and the relationship between knowledge of first and second pole. Among the main conclusions, we called attention that, in professional practice, the renormalizations arise after superior guidance is received and also arise based on what is specified in the prescribed norms. Therefore, we noticed the difference between the prescribed work and the actual one in the editorial craft. Editorial activity is permeated by pre-existing norms that, due to the individuality of each worker, extend beyond their role and are continuously redefined.